The Relationship Between Nurses' Perceived Organizational Support and Levels of Occupational Commitment - Serhat Aydoğmuş; Fatma Er (Association of Nurse Managers, 2023)
Aim: The aim of this study is to determine the relationship between nurses' perceived organizational support and their level of commitment to the occupational. Method: This research was conducted in relational descriptive type. 950 nurses working in a public university hospital constitute the universe of the research. The sample group consisted of 404 nurses who were haphazard selected from the non-probability sampling method, volunteered to participate in the research and worked in this institution for at least 6 months. The data of the research collected by 'Personal Information Form', 'Perceived Organizational Support Scale' and 'Occupational Commitment in Nursing Scale'. In the evaluation of the data, 'number, percentage distribution, mean, standard deviation, Cronbach Alpha coefficient, t test, one-way analysis of variance (ANOVA) and Pearson Correlation' analysis were used. Results: It was found that nurses' who participated the research, average Perceived Organizational Support Scale score was 23.54 (SD=6.83) and it was stated that nurses' perceived organizational support was at moderate level. Mean of The Occupational Commitment Scale in Nursing of nurses' who attended the research was calculated as 67.2 (SD=12.16) and this shows that nurses had medium level of occupational commitment. It was found statistically a significant correlation between points of Perceived Organizational Support Scale and Occupational Commitment in Nursing Scale at in the positive direction (p<0.05). Conclusion: It was determined that there was a moderate and positive correlation between the total score of the nurses' Perceived Organizational Support Scale and the Nursing Occupational Commitment Scale.